Gamaliel Churata Interpelaciones al excepcionalismo de los saberes universales desde una concepción ambiciosamente crítica del pensamiento humano - Monasterios Pérez, Elizabeth (Pubblicazioni di América Crítica, 2020)
Churata is an author who, from a place of enunciation removed from the shaping processes of Western modernity such as the Andean plateau, opens and will continue to open new interpretive paths from unprecedented perspectives. "He dialogues with the various turns taken by criticism and cultural theory in recent decades," as Elizabeth Monasterios shows in the introduction, and new generations of critics of Latin American literature and culture are being formed through the study of his work. The book, which collects the papers of the International Conference "Gamaliel Churata: envisioning the circulation of andean epistemologies in the age of globalization," held at the University of Pittsburgh in 2016, marks a moment of transition in studies on the author from which emerges as a challenge: "The urgency of publishing the unpublished manuscripts and reflecting on the theoretical and conceptual potential of his work to contribute, from an andean epistemology, to the current debate, on humanism and the construction of new ontological consciousnesses".